Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 120254 by bramlexs22 last updated on 30/Oct/20

 ∫ (dx/(1+cosθ.cos x )) ?

dx1+cosθ.cosx?

Answered by TANMAY PANACEA last updated on 30/Oct/20

∫(dx/(cosθ(secθ+cosx)))  (1/(cosθ))∫(dx/(secθ+((1−tan^2 (x/2))/(1+tan^2 (x/2)))))  (1/(cosθ))∫((sec^2 (x/2))/(secθ+secθtan^2 (x/2)+1−tan^2 (x/2)))  (1/(cosθ))∫((d(tan(x/2))×2)/((1+secθ)+(secθ−1)tan^2 (x/2)))  (2/(cosθ))∫(dk/((1+secθ)+(secθ−1)k^2 ))  (2/(cosθ(secθ−1)))∫(dk/(k^2 +((1+secθ)/(secθ−1))))  (2/(1−cosθ))×(1/( (√((1+secθ)/(secθ−1)))))tan^(−1) ((k/( (√((secθ+1)/(secθ−1))))))

dxcosθ(secθ+cosx)1cosθdxsecθ+1tan2x21+tan2x21cosθsec2x2secθ+secθtan2x2+1tan2x21cosθd(tanx2)×2(1+secθ)+(secθ1)tan2x22cosθdk(1+secθ)+(secθ1)k22cosθ(secθ1)dkk2+1+secθsecθ121cosθ×11+secθsecθ1tan1(ksecθ+1secθ1)

Answered by bemath last updated on 30/Oct/20

let cos θ = k ⇒ ∫ (dx/(1+kcos x))  let tan ((x/2)) = u ⇒ (1/2)sec^2 ((x/2))dx=du  dx = 2cos^2 ((x/2)) du = ((2 du)/(1+u^2 ))  I=∫ ((2 du)/((1+u^2 )(1+((k(1−u^2 ))/(1+u^2 )))))  I=∫ ((2 du)/((1+k)+(1−k)u^2 ))= ∫ ((2 du)/( ((√(1+k )))^2  +u^2  ((√(1−k)) )^2 ))  letting u(√(1−k)) = (√(1+k)) tan w  I= ∫ ((2 ((√((1+k)/(1−k))) ) sec^2 (w) dw)/((1+k)sec^2 (w)))  I=(2/( (√(1−k^2 )))) w + c = (2/( (√(1−k^2 )))) arc tan (u (√((1−k)/(1+k))))+c  = (2/( (√(1−cos^2 θ)))) arc tan (tan ((x/2))(√((1−cos θ)/(1+cos θ)))) + c  = 2 cosec θ arc tan (tan ((x/2)) (√((1−cos θ)/(1+cos θ)))) + c

letcosθ=kdx1+kcosxlettan(x2)=u12sec2(x2)dx=dudx=2cos2(x2)du=2du1+u2I=2du(1+u2)(1+k(1u2)1+u2)I=2du(1+k)+(1k)u2=2du(1+k)2+u2(1k)2lettingu1k=1+ktanwI=2(1+k1k)sec2(w)dw(1+k)sec2(w)I=21k2w+c=21k2arctan(u1k1+k)+c=21cos2θarctan(tan(x2)1cosθ1+cosθ)+c=2cosecθarctan(tan(x2)1cosθ1+cosθ)+c

Answered by mathmax by abdo last updated on 30/Oct/20

I =∫ (dx/(1+cosθ cosx)) =∫ (dx/(1+a cosx))  (a=cosθ ⇒∣a∣≤1)  =_(tan((x/2))=t)     ∫   ((2dt)/((1+t^2 )(1+a((1−t^2 )/(1+t^2 ))))) =∫ ((2dt)/(1+t^2 +a−at^2 ))  =∫ ((2dt)/((1−a)t^2  +1+a)) =(2/(1−a))∫  (dt/(t^2 +((1+a)/(1−a))))  =_(t=(√((1+a)/(1−a)))z)    (2/(1−a)).((1−a)/(1+a))∫  (1/(z^2 +1))((√(1+a))/(√(1−a)))dz  =(2/(√(1−a^2 ))) arctan(z) +c =(2/(∣sinθ∣)) arctan((√((1−cosθ)/(1+cosθ)))tan((x/2))) +C  I=(2/(∣sinθ∣)) arctan(∣tan((θ/2))∣tan((x/2))) +C

I=dx1+cosθcosx=dx1+acosx(a=cosθ⇒∣a∣⩽1)=tan(x2)=t2dt(1+t2)(1+a1t21+t2)=2dt1+t2+aat2=2dt(1a)t2+1+a=21adtt2+1+a1a=t=1+a1az21a.1a1+a1z2+11+a1adz=21a2arctan(z)+c=2sinθarctan(1cosθ1+cosθtan(x2))+CI=2sinθarctan(tan(θ2)tan(x2))+C

Answered by Dwaipayan Shikari last updated on 30/Oct/20

∫(dx/(1+Γcosx))        Γ=cosθ  =2∫(dt/(1+((Γ−Γt^2 )/(1+t^2 )))).(1/(1+t^2 ))  =2∫(dt/(t^2 (1−Γ)+(Γ+1)))=(2/(1−Γ))∫(1/(t^2 +((√((1+Γ)/(1−Γ))))^2 ))dt  =(2/( (√(1−Γ^2 ))))tan^(−1) t(√((1−Γ)/(1+Γ))) +C  =(2/( (√(1−cos^2 θ))))tan^(−1) tan(x/2).(√((1−cosθ)/(1+cosθ)))+C  (2/(∣sinθ∣))tan^(−1) ((tan(x/2))∣(tan(θ/2))∣)+C

dx1+ΓcosxΓ=cosθ=2dt1+ΓΓt21+t2.11+t2=2dtt2(1Γ)+(Γ+1)=21Γ1t2+(1+Γ1Γ)2dt=21Γ2tan1t1Γ1+Γ+C=21cos2θtan1tanx2.1cosθ1+cosθ+C2sinθtan1((tanx2)(tanθ2))+C

Terms of Service

Privacy Policy

Contact: info@tinkutara.com